Postharvest control of anthracnose lesions and its causative agent, Colletotrichum musae by some oils - Rizwana, Humaira (Cellular and Molecular Biology, 2018)
Anthracnose of banana is incited by Colletotrichum musae. It is recognized as one the most destructive diseases of mature and immature banana fruits, resulting in huge economic losses all over the world. Present research deals with screening some oils both in vitro and in vivo for their antifungal activity against C.musae. Clove oil (0.1µl/ml) completely arrested the conidial germination and mycelial growth of C. musae. Fenugreek and almond oil exhibited significant inhibition of mycelial growth, 61% and 57% at a concentration of 2µl/ml. However, olive oil was least inhibitory on the test fungi. Clove oil also a showed marked reduction in anthracnose lesions on banana fruits, thereby suggesting disease control. Scanning electron microscopy revealed severely damaged mycelium and conidia. FTIR studies show the presence of important bands representing phenols, terpenes, aldehydes, and ketones. Based on our findings; clove, fenugreek and almond oil demonstrated fungicidal and fungistatic activities against anthracnose pathogen. Hence, these oils can be considered as potential alternatives to chemical treatments.